PENERAPAN REALISTICS MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KETEKUNAN DAN PRESTASI BELAJAR SISWA - Dian Opinsi; Nina Kurniah (UNIB Press, 2022)
This study aims to improve student persistence and learning achievement using the application of Realistic Mathematics Education (RME) learning in mathematics subject matter in class V SD Negeri 72 Pagaralam. The research design used was classroom action research in the form of an action cycle consisting of planning, implementing the action, observing (observing) and reflecting, the design of this study also used a quasi-experimental study. The research subjects were students of class V.A (class PTK) even semester of the 2020/2021 school year SD Negeri 72 Pagaralam. The quasi-experimental sample was class V.B and class V SD Negeri 58 Pagaralam as the control class. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results showed that the application of Realistic Mathematics Education (RME) learning can improve the persistence and learning achievement of grade V students of SD Negeri 72 Pagaralam.